Monitoring of in-season neuromuscular and perceptual fatigue in youth rugby players - Oliver, J. L.; Lloyd, R. S.; Whitney, A. (European Journal of Sport Science, 2015)
The purpose of this study was to examine both short- and long-term neuromuscular and perceptual fatigue in youth rugby players during a seven-week in-season mesocycle. Eleven male youth rugby players (age 16.9 ± 0.8 years) were assessed for countermovement jump (CMJ), reactive strength index (RSI) and leg stiffness to monitor neuromuscular performance, together with a well-being questionnaire to monitor perceptual fatigue. Players trained and competed throughout a seven-week block with test variables measured at baseline and 24 h pre- and post-matches played in weeks 1, 4 and 7. Players trained on average 9.7 ± 1.1 h per week and competed in 10.5?±?1.9 games over the seven-week block. Pre- to post-match reductions were significant across all games for CMJ, RSI and well-being (all P < 0.05), ranging from likely to almost certain negative reductions. Well-being and RSI demonstrated non-significant (P < 0.05) unclear or inconsistent changes when comparing pre-match scores to baseline. Significant reductions to baseline were observed pre-match for CMJ (weeks 4 and 7) and stiffness (week 7), representing very likely to almost certain negative long-term decrements. CMJ, RSI and well-being were all sensitive to detecting post-match fatigue. Importantly, CMJ and stiffness were sensitive to detecting accumulated fatigue over a seven-week period, whereas RSI and well-being were not. Consequently, either a CMJ or leg stiffness should be monitored to detect long-term, accumulated fatigue in academy rugby players.